2011
DOI: 10.1021/ja207327v
|View full text |Cite
|
Sign up to set email alerts
|

Cfr and RlmN Contain a Single [4Fe-4S] Cluster, which Directs Two Distinct Reactivities for S-Adenosylmethionine: Methyl Transfer by SN2 Displacement and Radical Generation

Abstract: The radical SAM (RS) proteins RlmN and Cfr catalyze methylation of carbons 2 and 8, respectively, of adenosine 2503 in 23S rRNA. Both reactions are similar in scope, entailing the synthesis of a methyl group partially derived from S-adenosylmethionine (SAM) onto electrophilic sp2-hybridized carbon atoms via the intermediacy of a protein S-methylcysteinyl (mCys) residue. Both proteins contain five conserved Cys residues, each of which is required for turnover. Three cysteines lie in a canonical RS CxxxCxxC moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 32 publications
4
110
0
2
Order By: Relevance
“…Initial work on these enzymes showed that SAM acts both as a source of Ado-CH 2 · and as a methyl group donor in the methylation reactions (36). Later, extensive mechanistic and crystallographic studies revealed that RlmN catalyzes an initial S N 2 nucleophilic substitution reaction to methylate a cysteine residue on the enzyme and uses subsequent radical SAM-dependent chemistry to generate a methyl group on the rRNA substrate (37)(38)(39). In the latter reaction, the methyl group that is appended to the adenosine residue retains only two hydrogens from the original SAM-derived methyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Initial work on these enzymes showed that SAM acts both as a source of Ado-CH 2 · and as a methyl group donor in the methylation reactions (36). Later, extensive mechanistic and crystallographic studies revealed that RlmN catalyzes an initial S N 2 nucleophilic substitution reaction to methylate a cysteine residue on the enzyme and uses subsequent radical SAM-dependent chemistry to generate a methyl group on the rRNA substrate (37)(38)(39). In the latter reaction, the methyl group that is appended to the adenosine residue retains only two hydrogens from the original SAM-derived methyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Method 1 (compounds 2, 8, and 9): The methodology was similar to that reported previously (31). Mobile phase: The initial conditions included 95% solvent A (40 mM aqueous ammonium acetate, pH 6.0, with glacial acetic acid and 5% methanol) and 5% solvent B (methanol), 0.5-5 min up to 13% B, 5-6.5 min up to 27% B, 6.5-7.0 min up to 53% B, 7.0-7.5 min isocratic 53% B, 7.5-8 min down to 5% B, and 8.0-10.0 min reequilibration at 5% B.…”
Section: Methodsmentioning
confidence: 97%
“…Studies by Booker and co-workers (33,38,39) showed that during the first turnover of RlmN and Cfr, when overproduced and purified with the [4Fe-4S] cluster intact, exogenous SAM is not the source of the appended methyl group. When RlmN and Cfr reactions were run in the presence of [methyl-2 H 3 ]SAM and a 7-nucleotide RNA substrate, the methylated products were not enriched with deuterium.…”
Section: Class a Rs Methylasesmentioning
confidence: 99%